Social Impacts of Tourism in the Pantanos de Villa Wildlife Refuge (Peru) - Espinoza, Sophia (2025)
Protected areas (PAs) have a unique value that relies on their high biological and cultural diversity, as well as their scenic beauty. Thus, they attract a large flow of tourists with recreational and/or educational purposes. The profits obtained from tourism support the PAs' objective which is to preserve its natural and cultural resources and ensure its sustainable development, including the maximisation of benefits for the local communities. Nevertheless, inefficiencies in the tourism management of PAs can produce negative social outcomes, such as pollution or disparity in the distribution of economic benefits, negatively affecting residents' quality of life. The Pantanos de Villa Wildlife Refuge (PVWR) is one of the most visited PAs in Peru and the only one located in an urban environment, which represents a challenge in its sustainable tourism management, especially in the social aspect. This research analysed the social impact of tourism in the PVWR, as perceived by residents located in its buffer zone. The study applied a qualitative methodology based on semi-structured in-depth interviews to 14 residents that allowed them to share their personal experiences with the social impacts identified in the literature and one non-academic source of evidence of the population's comfort/discomfort with tourism. The study revealed 11 social impacts of tourism about which participants have a predominantly positive perception. For instance, participants agree that tourism promotes environmental education and improves public infrastructure, while a strong sense of belonging and pride was perceived among them. Nonetheless, participants have diverse perceptions of three social impacts, namely: employment and economic growth, citizen security, and opportunities for cultural exchange, possible indications of an unequal distribution of benefits or differing level of involvement of residents in the tourism activity. This is one of a few studies that addresses the impacts of tourism in PAs in Peru focusing on the social dimension, as most research focuses on the environmental one. In terms of practical contributions, the study suggests specific actions that the local authorities may apply to maximise the positive social impacts of tourism for all residents of the PVWR.